2013
DOI: 10.1038/onc.2012.636
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miRNA-155 promotes tumour angiogenesis by targeting VHL and is associated with poor prognosis and triple-negative breast cancer

Abstract: MicroRNA-155 (miR-155) is frequently up-regulated in various types of human cancer; however, its role in cancer angiogenesis remains unknown. Here, we demonstrate the role of miR-155 in angiogenesis through targeting von Hippel-Lindau tumour suppressor (VHL) in breast cancer. Ectopic expression of miR-155 induced whereas knockdown of miR-155 inhibited HUVEC network formation, proliferation, invasion, and migration. Furthermore, mammary fat pad xenotransplantation of ectopically expressed miR-155 resulted in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
248
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(258 citation statements)
references
References 52 publications
5
248
0
5
Order By: Relevance
“…Previous studies reported that TGF-β-mediated Smad4 expression induces miR-155 promoter activity and enriches miR-155 expression to contribute to cell migration and invasion (38), and found that NF-κB, STAT5, or CCAAT/enhancer binding protein beta (C/EBPβ) could bind to miR-155 promoter region and induce miR-155 expression in colon cancer, cutaneous T-cell lymphoma, or fat cells (20,39,40). miR-155 has been considered an "oncomicroRNA" by targeting several tumor suppressors, including SOCS1, FOXO3a, RhoA, C/EBPβ, PP2A/C, and von Hippel-Lindau tumor suppressor (VHL), and it has been found to promote the EMT, invasion, metastasis, growth, and angiogenesis of cancer cells (20,(41)(42)(43). In addition, the up-regulation of miR-155 has been reported to promote tumor angiogenesis by targeting VHL and is associated with poor prognosis for breast cancer (43); additionally, the loss of VHL has been reported to induce NF-κB activity (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that TGF-β-mediated Smad4 expression induces miR-155 promoter activity and enriches miR-155 expression to contribute to cell migration and invasion (38), and found that NF-κB, STAT5, or CCAAT/enhancer binding protein beta (C/EBPβ) could bind to miR-155 promoter region and induce miR-155 expression in colon cancer, cutaneous T-cell lymphoma, or fat cells (20,39,40). miR-155 has been considered an "oncomicroRNA" by targeting several tumor suppressors, including SOCS1, FOXO3a, RhoA, C/EBPβ, PP2A/C, and von Hippel-Lindau tumor suppressor (VHL), and it has been found to promote the EMT, invasion, metastasis, growth, and angiogenesis of cancer cells (20,(41)(42)(43). In addition, the up-regulation of miR-155 has been reported to promote tumor angiogenesis by targeting VHL and is associated with poor prognosis for breast cancer (43); additionally, the loss of VHL has been reported to induce NF-κB activity (44).…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 has been considered an "oncomicroRNA" by targeting several tumor suppressors, including SOCS1, FOXO3a, RhoA, C/EBPβ, PP2A/C, and von Hippel-Lindau tumor suppressor (VHL), and it has been found to promote the EMT, invasion, metastasis, growth, and angiogenesis of cancer cells (20,(41)(42)(43). In addition, the up-regulation of miR-155 has been reported to promote tumor angiogenesis by targeting VHL and is associated with poor prognosis for breast cancer (43); additionally, the loss of VHL has been reported to induce NF-κB activity (44). These findings support our results that miR-155 decreased VHL expression, which in turn activated NF-κB; this may contribute to the positive feedback activation of miR-155 and promote gefitinib resistance and cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of human breast cancer cell lines, ZR-75-1 and MCF-10A, showed that gain-of-function mutant p53 induces expression of miR-155, which inhibits TGF-β signaling by targeting ZNF652 to promote cancer cell invasiveness (Neilsen et al 2013). Moreover, validated miR-155 target transcripts in the context of breast cancer include both tumor-suppressor genes, like CEBP-β, FOXO3a, ZNF652, and VHL, and oncogenes, like BACH1 and SATB1 (Yin et al 2008;Kong et al 2010Kong et al , 2014McInnes et al 2012;Johansson et al 2013;Neilsen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed on the role and related mechanism of miRNAs in numerous different kinds of diseases (9)(10)(11)(12). miRNAs bind primarily to the 3'-untranslated region (3'UTR) of their target messenger RNAs (mRNAs) to reduce their stability and decrease the expression of target mRNAs at the post-transcriptional level (13), which play important roles in various biological processes including cell growth, proliferation, differentiation and death (14)(15)(16)(17)(18)(19). Concerning chemotherapy in various types of cancers such as breast cancer, lung adenocarcinoma, glioblastoma, and ovarian cancer, recent studies have shown that miRNAs also act in important roles (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%